Formação de pesquisadores na UFSCar e na área de Educação Especial: impacto do programa de iniciação científica do CNPq - Cabrero, Rodrigo de Castro (2007)
ABSTRACT The investments in Science and Technology have improved the quality of life. Researches dealing with persons with special educational needs had extended the knowledge about this population group and had supported the development of instructional strategies. However, it is necessary to increase the national scientific community to nourish new knowledge. The research shows the influence of the Institutional Scholarship Program for Undergraduate Students - PIBIC of the National Council for Scientific and Technological Development - CNPq, to breed the future generation of scientists in the Federal University of São Carlos - UFSCar and in the area of Special Education. The study evaluates the Science and Technology in Brazil and discusses the formation of a new generation of scientists. The research approach includes a general study examining Special Education in Brazil and an evaluation of advances coming from theses and dissertations in this area. The first study deals with the academic trajectory of former PIBIC students at UFSCar and their enrollments in graduate programs encompassing Master and Doctorate degrees. The research was done by searching each previous PIBIC student by name in the institutional homepage of the Coordination of Formation of Staff of Superior Level CAPES which contains information about everyone who had finished a Master and Doctorate degrees. The time period from 1992 to 2000 was searched. Additionally, the Lattes Curricula Vitae Database was checked for update information. These data allow to evaluate the results of the PIBIC in the UFSCar based on graduate studies concluded by former students and the institution that they had chosen to continue their academic life. The second investigation covered the period of August,1993 to July, 2004, and involved around 175,000 PIBIC Scholarships granted in different regions of Brazil. The focus was to find out scientific projects related to Special Education. A classification was generated taking into account the target population and the volume of research carried out in each institution. Afterwards, CAPES and CNPq databases was checked for verification of the academic trajectory after finishing undergraduate studies of the former PIBIC students that became involved with projects in Special Education area. Around 50% of the former PIBIC students at UFSCar started graduate courses and preferred to stay in São Paulo State. Only 0.64% of the projects with analysis conditions (145.028) fits the Special Education area. General studies are in the first position, followed by the analyses about mental deficiency and, finally, hearing impairments. The estimative is that at least 36% of the former PIBIC students will conclude graduate programs encompassing Master and Doctorate degrees. It is necessary to stimulate researches and design strategies to form new researchers in Special Education area. Further studies about PIBIC scholarships are highly recommended for a better understanding of their output.